2017
DOI: 10.4103/jehp.jehp_48_15
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a program on evidence-based dentistry in dental students

Abstract: INTRODUCTION:Evidence-based dentistry (EBD) is an approach to oral healthcare by combining the best scientific evidence and clinical diagnostics, clinical expertise of the dentist, and the patient's treatment needs and preferences. The aim of the present study is to evaluate the effectiveness of an education program on EBD offered in a community-dentistry course in improving knowledge and attitudes of students in this regard.STUDY METHODS:By a quasi-experimental study design, 64 senior dental students of Islam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 11 publications
0
15
0
Order By: Relevance
“…[ 18 ] In another study, the changes in attitude score were less in comparison to the knowledge scores. They obtained a medium size effect in their analysis[ 19 ] [ Table 3 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 18 ] In another study, the changes in attitude score were less in comparison to the knowledge scores. They obtained a medium size effect in their analysis[ 19 ] [ Table 3 ].…”
Section: Resultsmentioning
confidence: 99%
“…As Chiappelli concluded the most urgent and important of these is undoubtedly to craft and validate novel didactic and practical methodologies to teach EBD-both research and practice-to the next generation of dental researchers and clinical dentists and to optimize the integration of EBD in the dental curriculum. [ 25 ] A change in attitudes from negative to positive were found in Najafi's and Asgari's[ 19 ] study after intervention. Spallek et al .,[ 7 ] introduced the lack of students’ desire to use EBD in clinical practice as the reason for such negative attitudes.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the selected studies originated from North America, 27–30,33,38,40,41 followed by Middle‐Eastern universities 6,35,36,39,46 . Fourteen studies evaluated changes observed in a single group of participants after the implementation of an educational intervention, with no comparative analyses 6,27–30,32,37,39–44,46 .…”
Section: Resultsmentioning
confidence: 99%
“…Fourteen studies evaluated changes observed in a single group of participants after the implementation of an educational intervention, with no comparative analyses 6,27–30,32,37,39–44,46 . Alternatively, five studies compared parallel cohorts, 31,34–36,38,45 wherein either different educational interventions were comparatively evaluated, 31,34,38 or trained were compared with untrained students 35,36,45 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation